A Proposal for Wired City Television - Harold J. Barnett; Edward Greenberg (Washington University Law Quarterly, 1968)
This Article proposes that a national system of wired city television (WCTV), inexpensively interconnected, is the best avenue to more and more varied programs. Television would then have capacity and incentive to educate, inform, and entertain specialized interests as well as general interests and mass tastes. To put the matter as simply as possible, a system of wired city TV makes it possible to increase very greatly the number of operating channels available to almost all of the homes in the nation. The carriage of a television signal to the home from a local studio camera or tape machine then becomes far less expensive than now. Intercity connections would be accomplished as under present arrangements-microwave and cable-or could take advantage of the new satellite technology discussed by Leland Johnson. We try to show below that the great increase in availability of low-cost television channels would be a sufficient condition to insure significant increases in numbers of programs and diversity, and that other alternatives cannot accomplish this as well.
Keywords: Communications; Television programming